Metabolites, volatile compounds and in vitro functional properties during growth and commercial harvest of Peruvian lucuma (Pouteria lucuma) - Aguilar-Galvez A. (2021)
The objective of this work was to identify primary and secondary metabolites, volatile compounds, bioactive properties and physicochemical characteristics of lucuma fruit at two ripeness stages, before physiological maturity (bPM) and at physiological maturity (PM) or commercial harvest. The content of reducing sugars decreased, while starch content increased. Myo-inositol and vitamin C content decreased and increased, respectively as maturity stage advanced. The content of stearic acid decreased possibly related to the formation of unsaturated fatty acids and volatile compounds, especially aldehydes, such as 2-hexenal. In fact, key identified volatile compounds included 2-hexenal and hexanoic acid. Regarding secondary metabolites and functional properties, these significantly decreased as maturity stage advanced, only the total carotenoid content significantly increased (0.083–0.148 mg ?-carotene equivalent); and the total phenolic content (83.3 69.3 mg GAE/g dw), sterols (4.4–6.5 ?g ?-sitosterol/g dw, 0.74–0.86 ?g cycloartenol/g dw) and ?-amylase inhibitory activity were not influenced by the maturity stage. The presence of ?-amyrin (25.4 ?g/g dw), myo-inositol (3.17 mg/g dw) and ?-tocopherol (5.1 mg/100 g dw) stood out, so lucuma fruit could have potential as food with antioxidant, hypolipidemic, anti-hyperglycemic, and anti-inflammatory properties. © 2021 Elsevier Ltd